Experimental Study on Hydraulic Performance of the Hand-operated Cleaning Screen Filter - DU Siqi; HAN Qibiao; LAN Jinhui; GUO Zhixin; LI Hui; HUANG Xiuqiao (Guan'gai paishui xuebao, 2021)
【Background】 Drip irrigation has been one of the most effective irrigation technologies to improve the water use efficiency in the worldwide, however, the drippers are likely to be clogged by small particles of irrigated water. To alleviate this problem, technical filters are usually set up in the forepart of the drip irrigation system. The hand-operated cleaning screen filter is a new type of semi-automatic cleaning screen filter, which costs small energy and would not stop filtering while doing cleaning, and it is being gradually applied to the micro-irrigation engineering in China. 【Objective】 The objective is to analyze the performance of the hand-operated cleaning screen filter, including its head losses ( energy consumption) and cleaning capability, and thus to provide technical support for the selection of micro-irrigation filters. 【Method】 Two types of exiting hand-operated cleaning screen filters (A and B) were taken as the subjects. The head loss tests of filters under different flow rates with clean water were conducted to obtain the head loss curves; the performance tests using sand water mixture with different flow rates and sediment concentrations were conducted to analyze the filtering efficiency; the cleaning efficiency tests were also carried out using filter B to detect the cleaning ability. 【Result】 The head loss curves for cleaning water accorded with the power function. The head loss of filters for sand water mixture climbed with increase of flow rate and sediment concentration. The influence of flow rate on the head loss was more significant than that on the clogging degree, while the influence of sediment concentration on the clogging degree was as obvious as that on the head loss. For both 2 filters, the head loss for cleaning water was less than 2 m, the condition of 30 m3/h in flow rate and 0.08 g/L in sediment concentration resulted in more interceptions and 0~200 µm small particles. Filter A had more steady change of head loss and more interceptions, while filter B had slower change of head loss and clogging degree, as well as longer filtration cycle. After cleaning, the filtering screen was as clean as before, and the change law of head loss was basically the same as before as well. 【Conclusion】 The hydraulic and filtration performance of the hand-operated cleaning screen filter is excellent, and it is suggested that filters should be selected according to different irrigation requirements and water source conditions. Besides, more experiments could be conducted to analyze the interaction of flow rate and sediment concentration, thus to find out the best working conditions of different filters.